APPLICATION OF THE PICTURE AND PICTURE MODEL IN THE TEACHING OF EXPLANATION TEXT - Syaifullah Syaifullah; Any Runiaty (Balai Diklat Keagamaan Banjarmasin, 2021)
This study was based on students' difficulties with vocabulary when writing Explanation Text. Thus, the study is aimed to improve students’ vocabulary in writing explanation text using ‘Picture and Picture’ learning model in XI Accounting 1 SMK Negeri 3 Banjarbaru Academic year 2019/2020.Classroom Action Research is used in this study. The validity of the study is gained by having methodological triangulation that took data from class observation, students’ questionnaire, and vocabulary test. ‘Picture and Picture’ learning model is the learning model which uses picture series to help students’ understanding in elaborating their writing of the explanation text. This study proved an improvement in the learning process and the students’ vocabulary in writing explanation text by using ‘Picture and Picture’ learning model in two cycles. The teacher experienced an improvement in the skill of using media and teaching English skills. The students' average vocabulary score increased from 61.42 in cycle 1 to 69.76 in cycle 2. The classical success also improved from 66.67% students reached KKM of 70 in Cycle 1 to 80.95% in cycle 2.